IT IN EDUCATION: FORESIGHT 2020: ICT COMPETENCY, ENHANCING CITIZENS' MEDIA AND COMPUTER LITERACY - Tapio Varis (Universidade Feevale, 2019)
IT in education: Foresight 2020: ICT competency, enhancing citizens' media and computer literacy